Is there a relationship between the use of motorcycles and the level of development of countries? - Bastos, Suzana Quinet Andrade; Gama, Fabio; Assis, Tiana de Paula; Milosz, Matheus (Bulletin of Geography. Socio-economic Series, 2020)
Our paper aims to analyse the hypothesis that locations with a higher Human Development Index (HDI) present lower rates of motorcycle use. For this we use an econometric model for 117 countries on five continents for the years 2013, 2015 and 2018. We assume that when a country reaches a higher level of development, its population is more likely to experience improvements in the quality of life, which also affects the quality of individual transportation, public transport and roads. Increases in income discourage the use of motorcycles, mainly due to their low safety and comfort features. Our results indicate that rates of motorcycle use in countries increase as HDI rises, before reaching a maximum point and then declining. Therefore, this evidence suggests that a certain degree of development discourages the use of this means of transport in favour of others.